Моделювання структурних характеристик процесу формування маркетингової стратегії будівельного підприємства - Дикий, О. В. (Ways to Improve Construction Efficiency, 2012)
In article is designed adapted to modern condition of the development building market programme procedure simulation system-dynamic modeling, founded on quantitative and qualitative feature of the operation and developments operator building market integrated in structure of the estimation to efficiency to marketing activity in accordance with resourses base enterprise to building branch.